ENERGY EFFICIENCY AND FUEL–EMISSION CALCULATIONS FOR UZBEKISTAN’S THERMAL POWER STATIONS: A CASE STUDY ANALYSIS (The Journal of Interdisciplinary Human Studies, 2026)
This study presents detailed energy efficiency and emission calculations forfive major thermal power stations in Uzbekistan, quantifying their current performance,fuel consumption patterns, CO₂ emission levels, and improvement potential. Uzbekistan’spower sector relies heavily on natural gas-fired thermal generation, with approximately90% of national electricity produced by thermal power stations (IES), many of whichwere commissioned during the Soviet era and operate below design efficiency. Usingplant-level operational data, thermodynamic heat balance analysis, and IPCC emissionfactor methodology, this study calculates the specific fuel consumption (SFC), thermalefficiency, and CO₂ emission intensity for each station. Results reveal that the analyzedstations operate at thermal efficiencies of 28–42%, with SFC values ranging from 290to 430 g.c.e./kWh, and emission intensities of 520–780 kg CO₂/MWh. Modernizationscenarios demonstrate that upgrading aging equipment and implementing combinedcycle technology could improve fleet-average efficiency from 33.4% to 48.5%, yieldingannual fuel savings of 3.2 billion m³ of natural gas and CO₂ emission reductions of12.8 million tonnes. These calculations provide a quantitative basis for investmentprioritization and energy policy planning in the Uzbekistan power sector
Keywords: Uzbekistan, thermal power station, IES, energy efficiency, specific fuel consumption, CO₂ emissions, combined cycle, modernization, natural gas